(untitled) (Al-Mansour Journal, 2025)
Environmental crimes constitute a significant topic that impacts life on Earth, whether humans, animals, plants, air, or water. Their scope is not limited to the local or regional level, but extends beyond that to take on an international dimension. Therefore, the current study sheds light on environmental crimes, both in terms of terminology and definition, as well as the forms of these crimes. It delimits the bases for considering such crimes as cross boundary, in addition to specifying the extent of environmental damage. The study also addresses the determination of international criminal responsibility in the event of their occurrence, in addition to the foundations for the establishment of this crime. The study ends up with a set of conclusions and recommendations.